How green-technology, energy-transition and resource rents influence load capacity factor in South Africa - Emmanuel Uche; Nicholas Ngepah (International Journal of Sustainable Energy, 2024)
ABSTRACTClimate change is gradually rising to a level that portends an existential threat to humanity. Nevertheless, environmental modellers, particularly in South Africa, still rely on restrictive environmental quality metrics for policy insights. Here, a comprehensive metric (load capacity factor [LCF]) that captures both the demand and supply sides of environmental qualities was activated. With the dataset (1970–2018), estimates of autoregressive distributive lag and quantile-ARDL underscored the varied effects of the selected factors on LCF. It was unravelled that green-technology significantly improved LCF only at the upper quantile but remained ineffective afterwards. Notably, LCF improved substantially at some quantiles following the transition to clean energy. Resource rents promoted LCF partially at the upper and middle quantiles but ineffective towards the lower quantile of the distributions. Economic growth improved LCF within the upper and middle quantiles, whereas it minimised LCF at the upper quantiles. We have provided relevant policy insights therein.